2014
DOI: 10.1002/2014ja019919
|View full text |Cite
|
Sign up to set email alerts
|

Intense duskside lower band chorus waves observed by Van Allen Probes: Generation and potential acceleration effect on radiation belt electrons

Abstract: Local acceleration driven by whistler mode chorus waves largely accounts for the enhancement of radiation belt relativistic electron fluxes, whose favored region is usually considered to be the plasmatrough with magnetic local time approximately from midnight through dawn to noon. On 2 October 2013, the Van Allen Probes recorded a rarely reported event of intense duskside lower band chorus waves (with power spectral density up to 10 −3 nT 2 ∕Hz) in the low-latitude region outside of L = 5. Such chorus waves ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…A recent study by Su et al [2014], showing that a lower band chorus observed also by Van Allen Probes was associated with anisotropic electron fluxes at energies above a few keV (what we call a hot component), is consistent with the hypothesis. A statistical study of more chorus events of different types and their correlation with electron pitch angle distributions would further test the validity of the hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study by Su et al [2014], showing that a lower band chorus observed also by Van Allen Probes was associated with anisotropic electron fluxes at energies above a few keV (what we call a hot component), is consistent with the hypothesis. A statistical study of more chorus events of different types and their correlation with electron pitch angle distributions would further test the validity of the hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…The central frequency f m / f ce =0.156 is slightly smaller than that ( f m / f ce = 0.20–0.35) in some previous works [e.g., Horne et al , ; Thorne et al , ; Li et al , ; Xiao et al , ] but approximately consistent with that ( f m / f ce = 0.165) in our recent work [ Su et al , ]. The acceleration by quasi‐parallel chorus ( θ m =0°) has been widely investigated in the previous simulations [e.g., Horne et al , ; Albert et al , ; Thorne et al , ; Li et al , ; Su et al , ; Xiao et al , ], and the effect of oblique chorus ( θ m >15°) has been emphasized in the recent works [e.g., Artemyev et al , ; Mourenas et al , , ].…”
Section: Rapid Outward Extensionsupporting
confidence: 88%
“…It should be noted that the specific values of wave parameters can change to some extent in the different events. Here the amplitude B t =0.147 nT is larger than that ( B t =0.05nT) from statistical analysis [e.g., Horne et al , ], smaller than that ( B t = 0.5–3 nT) in some extreme event [e.g., Cattell et al , ; Santolík et al , ; Su et al , ], but generally comparable to that ( B t = 0.1–0.2 nT) for some recent event [e.g., Thorne et al , ; Li et al , ; Xiao et al , ]. The central frequency f m / f ce =0.156 is slightly smaller than that ( f m / f ce = 0.20–0.35) in some previous works [e.g., Horne et al , ; Thorne et al , ; Li et al , ; Xiao et al , ] but approximately consistent with that ( f m / f ce = 0.165) in our recent work [ Su et al , ].…”
Section: Rapid Outward Extensionmentioning
confidence: 84%
See 1 more Smart Citation
“…Specifically, the electron density is assumed to be n e = a 1 exp(bx) + a 2 exp(cx), where x = (V 1 + V 2 )∕2 is the average of opposing antenna potentials over a spin period (∼11 s) of the spacecraft, and a 1 , a 2 , b, and c are constants determined by fitting to the density data from the EMFISIS suite. Chorus emissions with a gap at 0.5f ce were excited by the anisotropic hot electrons near the magnetic equator (e.g., W. Li et al, 2009;Su et al, 2014;Tsurutani & Smith, 1977, 1974 and propagated quasi-parallel toward higher latitudes. For ULF pulsations, only the two electric components in the spin plane of the satellite are available, and we derive the third component along the spin axis from the assumption E · B = 0.…”
Section: Methodsmentioning
confidence: 99%